Mémoires empêchées, graines de fictions? - Michèle Leclerc-Olive (Funes)
To be unable to tell oneself, memory, like an ardent river, ends up sometimes by passing the obstacles put in to stem it. It then takes various forms trying to give itself a sustainable figure, both for the author and for the reader. This paper revisits the dichotomy fiction/no-fiction in the light of an anthropology of biographical experiences. Based on examples – the history of Quixote is only the best known – it proposes to go back to some experiments of incysted, hidden, truncated memories.